Vulnerability Evaluation of Mariculture System and Diagnosis of Obstacle Factors in Zhejiang Province - CHEN Fang; XU Shuru; FU Yufang; WANG Minhui (Haiyang Kaifa yu guanli)
Mariculture is a significant component of China's marine fisheries. To promote the sustainable and high-quality development of the mariculture industry in Zhejiang Province, a vulnerability assessment index system for the mariculture system was established, considering the dimensions of economy, society, and ecology, along with sensitivity and response capacity. The vulnerability assessment model of coupled human-environment system and the obstacle degree model were used to analyze the temporal evolution characteristics and obstacle factors of the vulnerability of the mariculture system in Zhejiang Province. The results indicate that: (1) The sensitivity index of the economic system is the highest; the response capacity index of the social system is the highest, and its vulnerability is the strongest; (2) The vulnerability trend of coupled human-environment system in Zhejiang Province changes obviously, taking 2011 as the limit, it can be divided into two stages of fluctuation decline and slow decline. (3) For the diagnosis of single index obstacle factors, the sensitivity of economic system and the response capacity indicators of the economic system have a relatively more prominent obstacle effect on the vulnerability of the coupled human-environment system. The order of subsystem obstacle degrees from large to small is as follows: economic system vulnerability, social system vulnerability, ecological system vulnerability.